COVID-19 vaccines portray the bright side of human creativity, but it means nothing until they prove their worth: A Study on Seroconversion after the first Dose of Covishield vaccine in central Kerala - Sangeetha Merrin Varghese; Arun Sachu; Linda Jacob; Geomcy George; George Mateethra Chandy; Abel K Samuel Johnson; Grace Mary John (Wolters Kluwer Medknow Publications, 2022)
Background: COVID-19 vaccines, we believe, have come to rescue us from the clutches of the dreaded severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). With rapid ongoing mutations, it is difficult to predict the effectiveness of seroconversion following vaccination. This study aims to find out the proportion of people with seroconversion following first dose of Covishield vaccine. Methods: Randomly selected health-care workers were followed up for SARS-CoV-2 immunoglobulin G (IgG) antibodies between 28 and 42 days after receiving their first vaccine dose. The VITROS SARS-CoV-2 IgG test (Ortho-Clinical Diagnostics, USA) with 100% specificity and > 90% sensitivity was used to assess seroconversion. Results: The first dose of vaccine induced seroconversion in 91.7% of beneficiaries. Nearly one-third (30.2%) of them had high antibody titers, and it showed a significant association with female gender (9.6 ± 5.5 vs. 7.6 ± 5.6) and younger age (P = 0.008). In addition, those with previous COVID infection showed a more robust immune response when compared to others (P = 0.001). Conclusion: Seroconversion rate of more than 90% offers a promising hope toward successful pandemic control. In the current scenario, the inability to attain the targeted coverage due to an upsurge in vaccine hesitancy, compounded with only lower proportion of seroconversion in elderly, faster rollout of the vaccines without any age limit, will help achieve the herd threshold more rapidly.